Effective Corporate Relations / Applying Public Relations in Business and Industry - Hart A. Norman (Mcgraw Hill Book Company, 1987)
This book demonstrates in practical terms what can be achieved by corporate relations, how, at what price, and over what period of time. Introduction, Corporate Goals and Strategies, Planning for Corporate Communications, Marketing Communications, Financial Public Relations, Effective Employee Communication, Local Community Public Relations, Parliamentary and EEC Relations, Building an International Reputation, Corporate Advertising, Sponsorship, Media Relations, Communications Research, Corporate Responsibility, Index.